2021
DOI: 10.3390/ijerph18073380
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Barriers and Enablers of Physical Activity among Female Emirati University Students

Abstract: Interventions to promote physical activity participation should reflect social and culturally relevant influences of the target demographic. The aim of this study was to explore perceptions of barriers to and enablers of physical activity participation among female Emirati university students. Five semi-structured focus groups were conducted (n = 25). Participants were asked open-ended questions about benefits, barriers and enablers of physical activity, and recommendations to promote participation. Emergent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Moreover, increasing age, lower education level, being female and married were also identified as obstacles. Similar results were reported by Burton et al25 about the barriers and enablers of physical activity among female university students from the United Arab Emirates.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, increasing age, lower education level, being female and married were also identified as obstacles. Similar results were reported by Burton et al25 about the barriers and enablers of physical activity among female university students from the United Arab Emirates.…”
Section: Discussionsupporting
confidence: 89%
“…Among others, lack of time was the most cited barrier to physical activity in university students. Although no previous systematic reviews have identified barriers to physical activity among university students, some qualitative studies have shown the presence of motivational and time-related barriers as factors preventing university students from practicing physical activity [ 122 , 143 , 144 ]. Furthermore, barriers to physical activity are almost similar in reviews on different populations, for example in individuals from the Middle East and North Africa [ 145 ], pregnant women [ 146 ] and medical services professionals [ 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested to provide vision care services to school-based children and adolescents as part of standard health care coverage from the Ministry of Education and Ministry of Health across all emirates, irrespective of household monthly income. While pursuing at least one outdoor activity was not shown to be significantly associated with self-reported needs for vision correction in this study, the warmer climate in the UAE may pose contextual barriers to pursuing outdoor activities, as suggested among women in a Qatari study [ 44 , 45 ]. Further research assessing the vision correction needs among adolescents in different climates in the UAE based on outdoor temperatures may help identify any associations between weather, pursuing outdoor activity, and vision correction needs.…”
Section: Discussionmentioning
confidence: 64%